Pengaruh Pendapatan dan Tingkat Pendidikan Orang Tua Terhadap Minat Melanjutkan Studi Ke Perguruan Tinggi: The Influence of Parents Income and Education Level on the Interest in Continuing Studies to Higher Education - Sukmawardani, Ami; Hermawan, Yoni; Aisyah, Iis (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aims to examine and identify the influence of parents' income and education level on the interest of twelfth-grade students at SMA Muhammadiyah Singaparna in continuing their studies to higher education. The research method used is an explanatory design. The sampling technique was saturated sampling, resulting in 97 respondents. Data was collected using a closed questionnaire, and the data analysis techniques included the normality test, linearity test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, the coefficient of determination (R²) test, t-test, and F-test. The results showed that: 1) There is an influence of income on the interest in continuing studies to higher education, with a significance value of 0.000 < 0.05. 2) There is an influence of the parents' education level on the interest in continuing studies to higher education, with a significance value of 0.005 < 0.05. 3) There is a simultaneous influence of parents' income and education level on the interest in continuing studies to higher education, with a significance value of 0.000 < 0.05.